Joint infrastructure and the sharing of benefits in the Senegal and Niger watersheds. Issue 6 (18th September 2016) - Tignino, Mara
ABSTRACT: Riparian states of the Senegal and Niger watersheds have developed specific techniques for the management of water infrastructure. A common feature in both watersheds is the sharing of benefits from water facilities. Niger River basin states are still at the beginning of a shared vision process for jointly managed infrastructure and equitable benefit sharing, while Senegal River basin states have led the way in innovative forms of shared ownership and governance. Environmental protection and public participation are increasingly included in the development of joint infrastructure, but more could be done to strengthen these aspects of river governance.